Marketer : a simulation - Smith, Jerald R.; Golden, Peggy A. (Boston : Houghton Mifflin, 1988)
This book is about: The decision-making process quiz on the manual; Decision incidents; ...
Keywords: Marketing; Management; Decision making; Management games; Marketing -- Decision making